(untitled) - Keillor, Garrison (Boston, 1998)
Edited by beloved storyteller Garrison Keillor, this year's volume promises to be full of humor, surprises, and, as always, accomplished writing by new and familiar voices. The preeminent short fiction series since 1915, The Best American Short Stories is the only volume that annually offers the finest works chosen by a distinguished best-selling author.
Keywords: American fiction,Short stories, american,Tiểu thuyết Mỹ,Truyện ngắn, Mỹ; 20th century,Thế kỷ 20